(untitled) (Research, Society and Development, 2020)
The aim of the present study was to evaluate the use of photobiomodulation therapy by LED (light emitting diode) in the functional activity of gait in animals with knee OA. For this, 20 male Wistar rats, two months old and with an average body mass of 150 g were used. OA (osteoarthritis) induction was performed on the left knee of all animals through the anterior cruciate ligament transection (ACLT). 4 weeks after OA induction, the rats were randomly divided into a control OA group (OAC): animals without any therapeutic intervention and an OA LED group (OAL): animals irradiated with LED. Gait assessment was performed before the start of LED treatment and after 4 weeks of LED treatment (850 nm, 200 mW, 30 sec, 6 J, 3 times a week). The analysis of gait did not lower the difference between the OAC and OAL group. Thus, it is necessary that an LED photobiomodulation therapy was not able to promote gait alteration in animals.